Assessment of the profitability of selected insurance companies: The case of the Republic of Serbia - Alihodžić Almir (Bankarstvo)
This paper aimed to examine specific factors that influence and have prognostic power on the profitability of selected insurance companies in the Republic of Serbia. Panel data were used for four insurance companies operating in the Republic of Serbia from 2013 to 2022, to estimate a linear model between the determinants that are theoretically expected to affect the performance and profitability of insurance companies. The findings of the paper revealed that company size according to all three methods (method of least squares, method of fully modified least squares, and robust method of least squares) has a significantly positive influence on the profitability of insurance companies. Also, the growth rate of the premium according to the fully modified least squares method has a positive (significant) impact on the profitability indicator, i.e. ROA. Seen from the other side, the weakest i.e., negative (significant) impact on the profitability of insurance companies in the Republic of Serbia was achieved by the independent variable expense ratio.